Dual‐Responsive Polydimethylsiloxane Networks. Issue 20 (9th September 2018) - Giebler, Michael; Radl, Simone Viola; Ast, Markus; Kaiser, Simon; Griesser, Thomas; Kern, Wolfgang; Schlögl, Sandra
ABSTRACT: Exploiting the salient features of o ‐nitrobenzyl chemistry, this work aims at the preparation of polydimethylsiloxane networks that undergo well‐defined bond cleavage in response to either UV light or different pH values as external trigger. Polydimethylsiloxane (PDMS) oligomers with terminal anhydride groups are thermally crosslinked in the presence of a bi‐functional epoxy monomer containing a photolabile o ‐nitrobenzyl ester ( o ‐NBE) group. The susceptibility of the ester groups toward hydrolytic cleavage reactions is used for a pH‐triggered network degradation. Sol–gel analysis confirms that the degradation time can be easily controlled by the base concentration over different time scales varying between hours and weeks. Along with classical ester hydrolysis, photoinduced degradation of the elastomeric networks is carried out by photoisomerization and cleavage of the o ‐NBE links upon exposure with UV light. Positive‐tone patterns with a structure size of 100 μm are obtained by photolithographic techniques confirming the spatial control of solubility properties. However, by increasing the exposure dose, recrosslinking of the networks is observed due to side reactions of the primary photocleavage products. As the reformed crosslinks are less sensitive to ester hydrolysis, the side reactions are employed to inscribe negative‐tone microstructures in the PDMS network. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2319–2329 Abstract : Dual‐responsive polydimethylsiloxane networks with o ‐nitrobenzyl ester links are prepared that undergo controlled cleavage in response to either UV light or different pH values. Hydrolytic network degradation is temporally controlled over different time scales by varying the base concentration. Photolysis proceeds rapidly within a few seconds. Spatial control of the photocleavage process enables the inscribing of well‐defined positive‐tone relief structures. At high exposure doses, negative‐tone patterns are obtained via a recrosslinking of primary photocleavage products.